The power of invisible leadership : how a compelling common purpose inspires exceptional leadership - Hickman, Gill Robinson; Sorenson, Georgia J.; Sage eBooks (Thousand Oaks, California : SAGE, 2016)
Exploring the concept that leadership is not about leaders or even leaders and followers, but about a much more dynamic and nuanced process, this is a compelling and unique text examining leadership as a dynamic and nuanced process.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 21, 2016).
Keywords: Leadership; Electronic books